Cognitive measures during walking with and without lower-limb prosthesis: protocol for a scoping review - Ming Liu; Jing Yuan; He Huang; Emily Cline; Jing Feng (BMJ Open)
Introduction Tuning of lower-limb (LL) robotic prosthesis control is necessary to provide personalised assistance to each human wearer during walking. Prostheses wearers’ adaptation processes are subjective and the efficiency largely depends on one’s mental processes. Therefore, beyond physical motor performance, prosthesis personalisation should consider the wearer’s preference and cognitive performance during walking. As a first step, it is necessary to examine the current measures of cognitive performance when a wearer walks with an LL prosthesis, identify the gaps and methodological considerations, and explore additional measures in a walking setting. In this protocol, we outlined a scoping review that will systematically summarise and evaluate the measures of cognitive performance during walking with and without LL prosthesis.Methods and analysis The review process will be guided and documented by CADIMA, an open-access online data management portal for evidence synthesis. Keyword searches will be conducted in seven databases (Web of Science, MEDLINE, BIOSIS, SciELO Citation Index, ProQuest, CINAHL and PsycINFO) up to 2020 supplemented with grey literature searches. Retrieved records will be screened by at least two independent reviewers on the title-and-abstract level and then the full-text level. Selected studies will be evaluated for reporting bias. Data on sample characteristics, type of cognitive function, characteristics of cognitive measures, task prioritisation, experimental design and walking setting will be extracted.Ethics and dissemination This scoping review will evaluate the measures used in previously published studies thus does not require ethical approval. The results will contribute to the advancement of prosthesis tuning processes by reviewing the application status of cognitive measures during walking with and without prosthesis and laying the foundation for developing needed measures for cognitive assessment during walking. The results will be disseminated through conferences and journals.